Hot Trends in Pheochromocytoma and Paraganglioma: Are We Getting Closer to Personalized Dynamic Prognostication? - C. Christofer JUHLIN; Ozgur METE (Federation of Turkish Pathology Societies, 2024)
Pheochromocytoma and abdominal paraganglioma (PPGL) are rare catecholamine-producing, keratin-negative, non-epithelial neuroendocrine neoplasms characterized by a unique association with syndromic diseases caused by constitutional mutations in a wide range of susceptibility genes. While PPGLs are recognized for their malignant potential, the risk of metastatic disease varies depending on several clinical, histological, and genetic factors. Accurate diagnosis and prognosis of these tumors require a multidisciplinary approach, integrating insights from various medical specialties. Pathologists play a crucial role in this complex task, as numerous morphological, immunohistochemical, and genetic findings can be linked to worse outcomes. Therefore, it is vital to stay informed about the latest advancements in PPGL pathology. This brief review provides an overview of the challenges associated with PPGLs and highlights the most recent developments in tumor prognostication.